1996
DOI: 10.1075/sl.20.3.03bis
|View full text |Cite
|
Sign up to set email alerts
|

Areal Typology and Grammaticalization

Abstract: Grammaticalization processes in East and mainland South East Asian languages show remarkable areal parallels within the domain of the verb and the noun. Since language contact increases processes of reanalysis it supports grammaticalization and its cross-linguistic similarity. Grammaticalization processes are governed by attractor positions (cf. 1.1.3.) and pathways of grammaticalization (cf. 1.1..4.). The former is a good parameter for making areal distinctions, the latter is of areal relevance only within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(36 citation statements)
references
References 0 publications
0
34
0
2
Order By: Relevance
“…Heine / Claudi / Hünnemeyer 1991, Bybee / Perkins / Pagliuca 1994, Bisang 1996, in jüngster Zeit auch in den Einzelphilologien aufgenommen und weiterentwickelt.…”
Section: Grammatikalisierung Kontexte Und Konstruktionenunclassified
“…Heine / Claudi / Hünnemeyer 1991, Bybee / Perkins / Pagliuca 1994, Bisang 1996, in jüngster Zeit auch in den Einzelphilologien aufgenommen und weiterentwickelt.…”
Section: Grammatikalisierung Kontexte Und Konstruktionenunclassified
“…they are bound morphs. An unresolved issue is whether those lexical morphemes which appear in a fixed position in a high number of complex words, always conveying the same meaning, are to be analysed as compound constituents or as derivational affixes, given the fact that it is often the case that in the languages of East and South-East Asia there is no (regular) formal distinction between lexical morphemes and grammatical morphemes (Bisang 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese xin can mean 'letter, letters, a letter, the letter, etc' according to a given context. This high degree of indeterminateness of nouns is a very important characteristic of East and Southeast Asian languages (Bisang 1993(Bisang , 1996 which is crucial to the existence of classifiers.…”
Section: Nouns Numerals and Number Markingmentioning
confidence: 99%
“…Greenberg (1975), for example, suggested that classifiers may evolve into gender or noun class markers, and a study by Hopper (1986: 342) indicates that in Malay classifiers may also serve as topic markers in that they typically occur with "potential topics". For a more extensive treatment of the grammaticalisation of classifiers the reader is referred to Bisang (1993Bisang ( , 1996. 23.…”
Section: Towards An Explanationmentioning
confidence: 99%